Integralidade do cuidado para pacientes brasileiros em hemodiálise: análise do acesso odontológico - Bruna Mara Ruas (2017)
Integrality is an important element in the guidance of public politics and health care, that considers peculiarities and the complexity of each individual. Patients with chronical renal insufficiency, conduct hemodialysis as a therapeutical measure for blood filtration and metabolite's removal. These patients present poor health conditions and low immunity, being exposed to several pathogens. The work of the Dental Group in a multidisciplinary association with other health professionals involved in the care of patients with renal insufficiency is one of the fundamental factors to improve the quality of life of a patient with this profile and avoid further complications that can become lethal. The current study aimed to analyze the integrality of the assistance, in the dimension of the dental access, to individuals with chronical renal insufficiency that have been in treatment at a hemodialysis service. The sketch of the study was cross sectional, with the sample of 467 patients in hemodialysis, between the ages of 19 to 90 years old. The data collection was conducted in two hemodialysis clinics of the Renal Therapy Institute of the Beneficent Evangelical Association of Minas Gerais, in the cities of Contagem and Belo Horizonte, Southeastern Brazil. The study was approved by the Ethical Committee in Research of the Federal University of Minas Gerais. The collection was carried in two phases: a survey by questionnaire and a clinical buccal. A pilot study was made after the phases of calibration intra and inter-examinator and phase of test/retest of the instrument. The clinical exam took place during a hemodialysis session of the participants, in their own hemodialysis chair, under artificial 7 light. The results showed an age average of 49.9 years old (± 13.7). The majority of the individuals from the male sex (58.0%) Black or brown skin color (82.7%), with less eight years of formal education advising to consult with a dentist (87.4%). The dental access in the last six months was identified between 130 patients (27.8%), although, the majority presented between one to twenty teeth with dental cavities (55.7%) and, therefore, were in need of dental treatment. The period in which the patient was in hemodialysis treatment, skin color, city where the participants live and the age where not variables associated to the dental access in the last six months. The individuals who had formal educations levels equal or superior to eight years (OR= 1.55, 95% IC= 1.09-2.41), no teeth with cavited dental caries (OR= 2.09, 95% IC= 1.36-3.20) and that received professional orientation to visit the dentist (OR= 2.16, 95% IC: 1.21-3.86) presented a higher chance of belonging to the group of patients who have visited the dentist in the last six months. The default of dental carie, the fact of having professional orientation to visit the dentist and have reached eight or more years of formal education were variables associated to dental access in patients with chronical renal insufficiency in hemodialysis.